Glass-Ceramic Foams from Alkali-Activated Vitrified Bottom Ash and Waste Glasses - Miroslava Hujova; Patricia Rabelo Monich; Jaroslav Sedlacek; Miroslav Hnatko; Jozef Kraxner; Dusan Galusek; Enrico Bernardo (Applied Sciences, 2020)
Both vitrified bottom ashes (VBAs) and waste glasses are forms of inorganic waste material that are widely landfilled, despite having some economic potential. Building on previous studies, we prepared glass-ceramic foams by the combination of VBA with either soda-lime glass (SLG) or borosilicate glass (BSG). Suspensions of fine powders in weakly alkaline solution underwent gelation, followed by frothing at nearly room temperature. Hardened “green” foams were sintered, with concurrent crystallization, at 850–1000 °C. All foams were highly porous (>70%), with mostly open porosity. The glass addition was fundamental in both gelation (promoting the formation of carbonate and silicate hydrated phases) and firing steps. While SLG addition enhanced the viscous flow sintering, without a significant impact on the crystallization of gehlenite, the main crystalline phase from the devitrification of VBA, BSG addition caused a reactive sintering, with remarkable changes in the phase assemblage. The glass addition generally also allowed lower sintering temperatures and yielded products with excellent crushing strength. However, only specific conditions resulted in the complete immobilization of pollutants (e.g., Cr3+ ions).